Optimalisasi Metode Pembiasaan 5 Kata Ajaib Dalam Membentuk Karakter Santun Pada Anak Usia 4-6 Tahun - Nur Hijriyati Waisa lilis; Masganti Sitorus (Jurnal Kajian Anak (J-Sanak), 2026)
This study was motivated by a lack of polite behavior among children aged 4–6 years, evidenced by infrequent use of polite language, inadequate social interaction skills, a lack of concern for peers, and insufficient responsibility in daily activities. The study aimed to enhance children's polite behavior through a method focusing on five key "magic words": please, sorry, thank you, may I, and go ahead. A Classroom Action Research (CAR) approach was employed, conducted over two cycles; each cycle comprised the stages of planning, action implementation, observation, and reflection. The research subjects consisted of 15 children aged 4–6 years at PAUD Al-Ikhsan. Data were collected through observation and documentation and subsequently analyzed using a descriptive quantitative method involving percentage calculations. The results indicate that the technique of habituating the use of the "five magic words" significantly improved the development of polite behavior in the children. This progress was reflected in the rise of the average percentage of polite character development: from 39.83% in the pre-cycle stage to 56.50% in Cycle I, and further to 83.83% in Cycle II. Furthermore, the children demonstrated more positive behavioral changes, such as habitually using polite expressions, apologizing for mistakes, expressing gratitude after receiving help, sharing with peers, and adhering to classroom rules regarding polite language. Thus, the "five magic words" habituation approach proved effective in instilling polite character traits during early childhood.